Early maladaptive schemas in chronically depressed patients: A preliminary investigation. (16th April 2018) - Flink, Niko; Honkalampi, Kirsi; Lehto, Soili M.; Viinamäki, Heimo; Koivumaa‐Honkanen, Heli; Valkonen‐Korhonen, Minna; Lindeman, Sari
Abstract: Background: Schema therapy has been proposed as a potentially effective treatment for chronic depression. However, little is known about early maladaptive schemas (EMSs), a key concept in schema therapy, in relation to chronic depression or chronic depression with comorbid personality pathology. The aim of the present study was to compare EMSs between currently chronically depressed patients with comorbid cluster C personality disorder (CDCPD ), currently chronically depressed patients (CD), and patients remitted from chronic depression (CDR ). Methods: Based on data from a naturalistic follow‐up study on psychiatric outpatients with major depressive disorder, three groups were formed according to Diagnostic and Statistical Manual of Mental Disorders‐IV: CDCPD ( n  = 15), CD ( n  = 23), and CDR ( n  = 13). Groups were compared in terms of background information and measurements for depression (Beck Depression Inventory) and EMSs (Young Schema Questionnaire). Results: Patients with CDCPD and CD did not differ in terms of background variables or the severity of depressive symptoms, but patients with CDCPD were more maladaptive with respect to the majority of EMSs. Patients with CDR were less depressed than CDCPD or CD patients, but did not differ in terms of EMSs compared with CD patients. Conclusions: Comorbid cluster C personality disorder appears to be associated with more severe EMS endorsement in chronically depressed patients. Remitted patients show similar cognitive vulnerability factors in terms of EMSs compared to those currently chronically depressed. The findings suggest that EMSs may contribute to vulnerability to chronic depression. Focusing on EMSs may be beneficial in the treatment of chronic depression.